INTEGRITAS SEBAGAI PEMODERASI PENGARUH SANKSI PAJAK DAN KESADARAN PADA KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Prawirasuta, Made Wisnu; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
Taxpayer compliance is an attitude or behavior of a taxpayer who caary out all obligations of taxiation. Issues regarding taxation compliance becomes important because disobedience taxation simultaneously will cause tax evasion attempts, resulting in reduced tax deposits to the State Treasury. This study aims to examine how the effect of the tax penalties and taxpayers on compliance awareness of an individual taxpayer with integrity as a moderating. The sampling is done through convenience sampling method, then the sample size is calculated using the formula Slovin by using a sample of 100. The data analysis method Moderated Regression Analysis (MRA). The results showed a positive effect of tax sanctions against individual taxpayer compliance Awareness taxpayer positive effect on compliance of individual taxpayers. The results also showed that integrity is able to moderate the effect of the tax penalties on an individual taxpayer compliance. Integrity also able to moderate influence on compliance awareness taxpayer individual taxpayer.
Keywords: Sanctions, Consciousness, Compliance and Integrity